Optimization of Digital Marketing Strategy with Implementation of SOSTAC Method - Jesi Irwanto; Wahyuning Murniati; Anisatul Fauziyah (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This training aims to develop digital marketing strategies for pesantren cooperative business entities as one of the efforts in countering the impact of the COVID 19 Pandemic. Design/methodology/approach: Qualitative phenomenological approach is this research approach where in the process of data collection is done with participant observation to gain an understanding of the essential phenomena that occur. Findings: The result of this research is a digital marketing strategy for Koperasi Pesantren where pendemic must further develop online marketing. Limited resources on understanding the mechanisms of online marketing become one of the main problems. This needs to be improved through a variety of relevant training activities. Research limitations/implications: This research is limited to Koperasi Pesantren Zain Amanah Maslahah Lumajang Regency. Practical implications: The results of this study can be a reference for other business entities to develop digital marketing strategies in the pandemic era. Originality/value: This paper is original Paper type: Research paper